Predicting cardiometabolic disease in medical students using FibroScan and 30-year Framingham risk scores - Sharma, Charu; Hashim, Muhammad Jawad; Yasin, Javed; Alnaqbi, Mahra Rashid Salim; Alkaabi, Abdulla Saeed Ahmed; Aldhaheri, Mohammed Saif Mohammed; Alkaabi, Juma; Agha, Adnan (Frontiers in Medicine, 2024)
function, biomarker analysis to calculate liver fibrosis risk, and subclinical atherosclerosis biomarkers. Liver stiffness measurements (LSM) and controlled attenuation parameter (CAP) values were measured using FibroScan 430 Mini to calculate liver fibrosis and steatosis, respectively. FS30 based on body mass index (FS30-BMI) and lipid levels (FS30-Lipid) were also calculated.Overall, 138 medical students participated in this study after providing informed consent. Using FS30-Lipid and FS30-BMI, CVD risk was identified in 2 (1.5%; n = 138) and 23 (17.6%; n = 132) individuals, respectively. MASLD fibrosis was identified based on FibroScan LSMs > 7.0 kPa in 12 medical students (9.4%, n = 128; 95% CI, 4.7-14.8%). Consumption of coffee and sugary soft drinks were predictive of liver fibrosis. In total, 36 students (28.6%; n = 128) were found to have hepatic steatosis based on FibroScan CAP values > 236 dB, and the predictive factors included increased body fat percentage, male sex, and lack of physical activity. Levels of inflammatory biomarkers, such as Creactive protein and lipids were not elevated in participants with MASLD. Discussion:CVD risk was identified in > 17% of young medical students. The frequency of liver fibrosis and steatosis was also high among the participants, indicating that liver damage starts at a relatively early age. Early intervention is needed among young adults via health promotion and lifestyle changes.